2012
DOI: 10.1002/ejoc.201200363
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Nickel‐Catalyzed Intermolecular [3+2+2] Cocyclization of Ethyl Cyclopropylideneacetate with Alkynes: DFT Calculations

Abstract: DFT investigations were employed to explore the complete reaction mechanism of the nickel‐catalyzed [3+2+2] cocyclization of ethyl cyclopropylideneacetate and alkynes. The lowest‐energy pathway involves the formation of a π complex between the methylenecyclopropane moiety and the nickel atom and occurs through a sequence of ring‐opening and ring‐closing reactions with C–C bond formation as the rate‐determining step. The crucial conversion of nickelacycloheptadiene to an eight‐membered nickelacycle was suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…7 Notwithstanding their inertness, carbon-carbon bonds may be cleaved via several different mechanisms in the presence of a transition-metal catalyst, including oxidative addition, β-carbon elimination, and retro-allylation. 8 Recent computational studies on C-C bond activation reactions focused on the cleavage of the polar C-CN bond 9 and the ring opening of strained vinylcyclopropanes, 10 cyclopropylidenes, 11 and cyclopropenones. 12,13,14 Computational studies from the Morokuma and Dang groups revealed that Rh-catalyzed ring opening of benzocyclobutenols and cyclobutanols takes place via deprotonation of the alcohol to form a Rh(I) alkoxide intermediate and subsequent β-carbon elimination (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%
“…7 Notwithstanding their inertness, carbon-carbon bonds may be cleaved via several different mechanisms in the presence of a transition-metal catalyst, including oxidative addition, β-carbon elimination, and retro-allylation. 8 Recent computational studies on C-C bond activation reactions focused on the cleavage of the polar C-CN bond 9 and the ring opening of strained vinylcyclopropanes, 10 cyclopropylidenes, 11 and cyclopropenones. 12,13,14 Computational studies from the Morokuma and Dang groups revealed that Rh-catalyzed ring opening of benzocyclobutenols and cyclobutanols takes place via deprotonation of the alcohol to form a Rh(I) alkoxide intermediate and subsequent β-carbon elimination (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a DFT study on the [3 + 2 + 2] cocyclization reaction was reported, in which the key step is oxidative cyclization of Ni(0) with two molecules of alkynes to generate a nickelacyclopentadiene (NCP). 7 Although the NCP mechanism can explain the experimental results of many Ni(0)catalyzed cocyclizations, 8,9 it cannot account for several features of the [3 + 2 + 2] cocyclization. In particular, the regioselectivity of [3 + 2 + 2] cocyclization depends markedly on the substituents of the alkynes (Scheme 1), and this cannot be explained in terms of the NCP mechanism (vide inf ra).…”
mentioning
confidence: 99%
“…Path A leads to the NCP CP3A-1a through two transition states (TSs), TS1A-1a and TS2A-1a, with reasonable activation barriers (Scheme 2), in good agreement with the previous calculation. 7 However, a second, unprecedented route, Path B (via nickelacycle CP3B-1a), turned out to be kinetically and thermodynamically more favorable (Scheme 3i). The initial π-complexation of Ni(PMe 3 ) 2 with CPA (CP0-2a) is likely to occur preferentially to that with ethyne (CP0-1a), being favored by ca.…”
mentioning
confidence: 99%
“…A mechanistic picture including the potential energy surfaces, energetic and the nature of equilibrium structures is very important to describe the nature of reaction pathways. However, computational investigations on the carbon–carbon bond activation by transition metals are limited to the C–CN bond and some special substrates …”
Section: Introductionmentioning
confidence: 99%